Assessment of Microbiological Indoor Air Quality in Cattle Breeding Farms - Justyna Szulc; Małgorzata Okrasa; Katarzyna Dybka-Stępień; Michael Sulyok; Adriana Nowak; Anna Otlewska; Bogumiła Szponar; Katarzyna Majchrzycka (Aerosol and Air Quality Research)
Abstract This study, which was conducted on a farm in central Poland from February till April 2019, aimed to evaluate microbiological threats on cattle breeding premises by counting and identifying the microorganisms (via culturing and high-throughput sequencing), assessing the endotoxin concentrations (via gas chromatography-mass spectrometry [GC-MS]) and analysing the secondary metabolites (including mycotoxins) in the air and sedimented dust (via liquid chromatography-tandem mass spectrometry [LC-MS/MS]) in six barns. In addition, the cytotoxicity of the dust to the human epithelial lung cell line was determined by using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. The concentrations of the total dust in the barns ranged from 0.175 to 0.351 mg m−3, with the dominant fraction (67.4-96.4%) displaying an aerodynamic diameter of < 1 µm. The bacterial and fungal concentrations fell between 7.14 × 103 and 3.88 × 104 CFU m−3, and 5.53 × 101 and 1.30 × 104 CFU m−3, respectively. The microbial population measured in the air and that in the settled dust exhibited a linear relationship, with an R2 of 0.8349–0.9471. We detected 172 and 210 bacterial/archaeal genera and 89 and 43 fungal genera in the dust and in the air, respectively. The dust samples were found to contain endotoxin concentrations of 98.98–178.31 nmol LPS mg−1 and a cytotoxicity of 5.66–13.99 mg mL1. High-throughput sequencing revealed extensive biodiversity in the microorganisms, which hitherto has not been reported for cattle farms. Of the identified species, those belonging to the genera Bacteroides, Corynebacterium, Staphylococcus, Ruminococcus, Aspergillus and Cladosporium potentially affect human and cattle health. Furthermore, the dust contained 113 chemical compounds, including characteristically fungal metabolites, bacterial metabolites, phytoestrogens and antibiotics. Future research should focus on the epidemiology of farmer exposure to the harmful biological agents discovered in this study.